Coining images of power : patterns in the representation of Roman emperors on imperial coinage, A.D. 193-284 - Manders, Erika. (Impact of Empire, 2012)
Current scholarship on Roman imperial representation addresses both the ways in which individual rulers presented themselves to their subjects and how particular aspects of imperial representation developed over time. This book combines these two approaches. It examines the diachronic development of the representation of Roman imperial power as a whole in one medium over a longer period of time. Through a quantitative and qualitative analysis of coin types issued between A.D. 193 and 284, patterns in the representation of third-century Roman emperors on imperial coinage are made visible. The result is a new perspective on the development of imperial ideology in times of crisis.